Communication of Teacher and Students in Religion Lesson - Dzenuškaitė, Stasė (Acta Paedagogica Vilnensia, 2001)
Reforming Lithuanian school should also involve efforts to discover more effective ways to foster morality and citizenship. Thus, the raising number of teens• crimes, drugs abuse or even suicides indicate about threatening situation of school students. The aim of this article is to discuss the possible implications of pedagogical communication in religion lesson. The basis for such perspective derive from literature studies, as well as from observing many religion les sons, talking with students and their teachers, written works of students and some test results. The article emphasize the role of pedagogical communication and interaction which could be considered as a basis of entire pedagogical process. The importance of transpersonal communication and I-You relations fostering is also stressed in words and writing of many ancient philosophers, as well as in the works of later and contemporary thinkers and educators. It is based also in Christian tradition, which invite to transform the old person to new one. According to many Christian authorities, Christian perfection – perfectio christiana – should be hold as the aim of Christian formation, thus communication in the spirit of love is an important precondition of Christian approach to others. Realizing these principles should help teachers to communicate with their difficult students and to understand them better, altogether to awaken the best in their souls. The article resume with hope that authentic Christian approach would make the teachers•influence to the students more positive.
Keywords: communication; interaction; Christian education; religion lesson.